VD_FINDINFO Pron / 2010 / 114 vom 4. November 2010 - VD Tribunal cantonal (2010)
EXÉCUTION FORCÉE, EXPULSION DE LOCATAIRE, PROCÈS DEVENU SANS OBJET | 121 CPC, 122 al. 1 CPC, 122 al. 3 CPC, 489 CPC, 21 al. 1 LPEBL, 22 LPEBL